The Impact of Brand Activism on Consumer Loyalty among Generation Z: An Analytical Study of the Relationship between Social Values and Purchasing Decisions - Bessas, HOCINE; Khalifa, Khaldi; Tedjani, KERROUCHE; Amara, SALIM Ben (Journal of Ecohumanism, 2025)
The study aims to measure the impact of brand activism on consumer loyalty among Generation Z by analyzing the relationship between brands' adoption of social and political issues and purchasing decisions. It adopted a descriptive analytical approach using an electronic questionnaire consisting of 25 statements (5 themes) distributed to a sample of 384 individuals from Generation Z in the Algerian context. The statistical results showed a high level of agreement on the preference for brands committed to environmental and social issues, with a clear distinction between genuine activism and marketing exploitation. All four hypotheses were accepted: the impact of brand activity on loyalty and word-of-mouth advertising, Generation Z's ability to distinguish between authenticity and exploitation, a strong relationship between the sincerity of the activity and trust, and the impact of provocative political stances on purchase intent. The study recommends that brands ensure consistency between their advertising discourse and internal practices, and focus on ongoing commitment to avoid losing the trust of this conscious generation. The results contribute to understanding modern market dynamics and guiding marketing strategies towards a sustainable value model.